6-(4n-1)=2-5n

Simple and best practice solution for 6-(4n-1)=2-5n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(4n-1)=2-5n equation:


Simplifying
6 + -1(4n + -1) = 2 + -5n

Reorder the terms:
6 + -1(-1 + 4n) = 2 + -5n
6 + (-1 * -1 + 4n * -1) = 2 + -5n
6 + (1 + -4n) = 2 + -5n

Combine like terms: 6 + 1 = 7
7 + -4n = 2 + -5n

Solving
7 + -4n = 2 + -5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '5n' to each side of the equation.
7 + -4n + 5n = 2 + -5n + 5n

Combine like terms: -4n + 5n = 1n
7 + 1n = 2 + -5n + 5n

Combine like terms: -5n + 5n = 0
7 + 1n = 2 + 0
7 + 1n = 2

Add '-7' to each side of the equation.
7 + -7 + 1n = 2 + -7

Combine like terms: 7 + -7 = 0
0 + 1n = 2 + -7
1n = 2 + -7

Combine like terms: 2 + -7 = -5
1n = -5

Divide each side by '1'.
n = -5

Simplifying
n = -5

See similar equations:

| 4=10y | | z-2(z+1)=3z-(20-5z) | | 3x+6=6-x | | p^2-12p+45=0 | | x^2+2x^2-900=0 | | 4/25•2/5= | | 4(2x+5)=-17+5 | | 1 = c2 | | q+7=9 | | 7r=60-5R | | 3 = d2 | | 7-4(4-(3y-7))=0 | | F(4)=x+9 | | 16y^3/20y^4 | | -45=-3x+18 | | 5a^2-a-20=0 | | -7/2x=-28 | | 3w^2-7w=6 | | (x-1+3i)(x-1-3i)=0 | | -3(5x+6)=-84 | | 1:1000/1:100×250 | | -4(-5x+6)=84 | | 2t=t+15 | | -6(3x-8)=102 | | 6-3x=9x | | -15-3x=-6x+27 | | 1/c=0.15 | | 6x-10=14+2x | | (s-4)(2s+2)(s^2-2)= | | 5x-34=74-4x | | 162x-82=738 | | 4(3n+3)=7(6n+7)+1 |

Equations solver categories